Epidermal Cell Fate Determination in Arabidopsis: Patterns Defined by a Steroid-Inducible Regulator - Lloyd, Alan M.; Schena, Mark; Walbot, Virginia; Davis, Ronald W. (Science (American Association for the Advancement of Science), 1994)
The Arabidopsis mutant ttg lacks both trichomes (epidermal hairs) and anthocyanin pigments. Trichomes and anthocyanins are restored by the constitutive expression of the maize transcriptional regulator (R). The expression of an R-glucocorticoid receptor chimeric protein results in a steroid hormone-dependent, conditional allele of R that functions in whole Arabidopsis plants. The response of the chimeric protein to pulses of hormone was used to define the pattern and timing of trichome formation on the developing leaf epidermis. Each adaxial epidermal leaf cell appears to have an equal probability of differentiating into a trichome; there is a temporal zone of decision for trichome cell fate that proceeds as a wave from the tip to the base of developing leaves.